(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This study systematically examines the psychological conditions that enhance the effectiveness of the upbringing (character-building) process in educational institutions. Its primary aim is to optimize, from a psychological standpoint, the formation of moral and ethical qualities in young learners and to develop practical, evidence-based recommendations for practitioners. Key factors identified as critical conditions for effective upbringing include a motivating environment, professional competence of teachers and mentors, a positive socio-psychological climate, cooperative teaching methods, sustained emotional support, and structured reflection mechanisms. The research employed observation, questionnaires, psychological tests, semi-structured interviews, and experimental trials. Findings demonstrate that maintaining a psychologically safe environment and applying a learner-centered approach significantly improve the effectiveness of upbringing activities. Based on these results, methodological guidelines were developed to strengthen the psychological climate, boost motivation, and foster communication grounded in mutual respect.